Identifying Key Driving Factors and Critical Uncertainties in the Future of Non-Formal Foreign Language Education Industry in Jabodetabek, Indonesia - Ellisa Vista Thenu; Yos Sunitiyoso (EduInovasi: Journal of Basic Educational Studies, 2025)
The rapid evolution of technology and social media influence, added with the dynamic of consumer behavior and possibility of change in policy and regulation, have brought about consequential uncertainties to the non-formal foreign language education industry in Jabodetabek, Indonesia. Scenario planning approach is used in this research to guide stakeholders in preparing the future. The time frame referred in this study is from 2030 to 2035 (5 to 10 years from the time this paper was written), a period deemed to be short to medium term. Eleven key driving factors were identified from this study through qualitative analysis and were assessed using a PESTEL framework. Following the qualitative analysis, rating method was conducted and two critical uncertainties for this industry were identified, they are “affordability & economic condition”, and “consumer-driven demand”.